The Scope and Challenges of Medical Biochemistry - Biswas, Subrata Kumar; Choudhury, Subhagata (Bangladesh Journal of Medical Biochemistry, 2018)
Abstract not available Bangladesh J Med Biochem 2016; 9(1): 3-4